Homework and minority students in difficulty with learning mathematics – the influence of public discourse - Lange, Troels (NOMAD Nordic Studies in Mathematics Education, 2008)
In this paper, I contrast an immigrant 10 years old girl’s perception of her home support and her mathematics teacher’s rather different perception. I show how the girl tries to align her perception of her home support with middle class Danish family values, and how the public discourse about immigrants apparently frames the teacher’s per- ception of the resources that are available or not available to the girl. The analysis becomes an example of how mathematics teaching and learning are embedded in a wider socio-political field. It suggests that sometimes resources could be available that schools do not see because students are constructed as disadvantaged.